2018
DOI: 10.1021/acs.jpcc.7b12656
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Capacity Fading of MgH2 Conversion-Type Anodes via Structural Morphology Changes and Electrochemical Impedance

Abstract: Previous studies have demonstrated that MgH2 is a promising conversion-type anode toward Li with high capacity (2037 mAh/g) and low discharge/charge overpotential-hysteresis. A major challenge is the capacity loss after few cycles. To improve the understanding of the complex conversion mechanism at the electrode/electrolyte interface and of its possible evolution, a systematic investigation of the morphology-property relation is undertaken. A multitude of MgH2 materials are obtained by mechanical milling using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…TEM analysis indicates that the 24 h milled MgH 2 powders have an average particle size of about 150 nm. 8,9 The starting hand-mixed CoO powders are in the micron range. However, aer Spex-milling, Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TEM analysis indicates that the 24 h milled MgH 2 powders have an average particle size of about 150 nm. 8,9 The starting hand-mixed CoO powders are in the micron range. However, aer Spex-milling, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…4,6 However, the reversible capacity is still limited owing to the poor conductivity of the involved entities (MgH 2 /LiH), along with transient aging issues of LiH in carbonate-based liquid electrolytes. [7][8][9] Using amorphous 80Li 2 S-20P 2 S 5 as a solid electrolyte (SE), Ikeda et al 10 reported $31% reversible capacity for MgH 2 for the 1 st cycle at room temperature, compared to $75% for liquid electrolytes. 6 Possible interaction at the electrode/SE (80Li 2 S-20P 2 S 5 ) interface is pointed out as a cause for the low reversible capacity.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the energy density, other reactions are foreseen like alloying with highly capacitive elements (Si, Sn) or conversion reactions [271]. For the latter, metallic hydrides have shown over the past decade that they offer an interesting alternative to other materials [272][273][274][275][276]. This was first demonstrated by Oumellal et al [277] that established the following conversion reaction:…”
Section: Libs Accommodating Metal Hydrides As Anodes and Electrolytesmentioning
confidence: 99%
“…Metal hydrides have been considered as potential anode materials for Li-ion batteries due to their large capacities and low average potential value versus Li + /Li 0 . Since the discovery of the electrochemical activity of metal hydrides towards lithium, MgH2 (theoretical capacity ~2000 mAh g -1 ) remains the most studied in this category of anodes for LIBs using a carbonate-based liquid electrolyte [17,18,[342][343][344][345][346][347][348][349].…”
Section: Metal Hydride Electrodes For Libsmentioning
confidence: 99%
“…NiMH [15,16]). Owing to their light-weight, low voltage and small hysteresis compared to oxide anodes, metal hydrides are now intensively studied for their applications as high energy density electrodes for LIBs with carbonate-based liquid electrolytes [17][18][19]. In addition, complex metal hydrides are studied for their application as solid-state electrolytes in next-generation all-solid-state batteries [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%